O desenvolvimento da política de educação permanente em saúde no estado de Mato Grosso - Cunha, Josiéd Marprates (2014)
The Permanent Education in Health is the topic of this dissertation, which set as main objective to analyze the development of Permanent Health Education in the State of Mato Grosso policy in the period 2003 to 2013, trying to understand, from the perspective of wholeness and historicity in Permanent Education. We conducted a qualitative study in which the methodological tool was a semi-structured interview, added to documental study was conducted with the School of Public Health and the Committee on Integrating Service-Learning (CIES) of the state. We sought understand the movement of education and health and the articulation of these two public policies in the training of health workers process. The analysis of the information generated showed discontinuity in the development of training policy for healthcare workers process and especially the prioritization of institutional interests to the detriment of the processes of collective construction of transformative practices. The analyze also showed as the Permanent Health Education was developed in Mato Grosso, since the creation of the Polo Training teams of the Family Health Program, through Polo Continuing Education in Health, the creation of regional CIES, after GM/MS ordinance No. 1996/2007, and coming to the present day, when public health suffered a setback due to the current government for its privatization option. The main contribution of this study was to allow us to understand that, from its inception until today, training in health policy has gone through advances and setbacks in the State in view of the correlation of forces that permeates government actions and causing it to oscillate and become effective in accordance with the political will of those who assume the management at the State Department of Health.